PERSEPSI PENILAIAN HAK DAN KEWAJIBAN KETENAGAKERJAAN ISLAM PERSPEKTIF CHAUDHRY PADA KARYAWAN BANK JATIM SYARIAH1) - Evita Febriani Ludiyatno; Eko Fajar Cahyono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the assessment of the rights and obligations of Islamic laborers from the perspective of Chaudhry. Employee rights include receiving the same treatment, getting a price specialization, being treated well, getting the right salary, not given a job beyond his ability, getting medical assistance. Whereas employee obligations include having a sincere and uplifting spirit and having a good religious nature case studies on the employees of Bank Jatim Syariah Central Surabaya and Sidoarjo. This research uses a quantitative descriptive approach with simple tabulations.Keywords: rights, obligations, Employee